2020
DOI: 10.1097/j.jcrs.0000000000000044
|View full text |Cite
|
Sign up to set email alerts
|

Visual performance and positional stability of a capsulorhexis-fixated extended depth-of-focus intraocular lens

Abstract: Purpose: To examine the 6-month outcomes of visual performance and positional stability of a capsule-fixated intraocular lens (IOL), FEMTIS Comfort MF15, extended depth-focus (EDOF) version, after cataract surgery performed using femtosecond laser-assisted cataract surgery capsulotomy. Setting: Vision Eye Institute, Sydney, Australia. Design: Prospective open-label postregistration data collection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…A halo is defined as a blurred circle surrounding the image of the light source. Starburst is defined as rays radiating outward from the central point of the source of light [ 3 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A halo is defined as a blurred circle surrounding the image of the light source. Starburst is defined as rays radiating outward from the central point of the source of light [ 3 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent clinical study that reported outcomes of the Femtis Comfort [ 21 ] confirms that this IOL offers a very good functional range of vision and minimal unwanted visual phenomena. In fact, another objective of having a smaller addition was to reduce the “angel wing glare effect”, reported for other IOL models with the same design, but with a larger Add value [ 22 ].…”
Section: Discussionmentioning
confidence: 88%
“…The femtosecond laser can however contribute to the optimization of the IOL position and opens new possibilities. 7,8 A recently published article assessed differences in effective lens position (ELP) based on the lens design. 8 Intraocular lenses (IOLs) with plate-haptic, c-loop haptic, and a rhexis-fixated lens were compared.…”
Section: Discussionmentioning
confidence: 99%
“…(6) How was the behavior of capsulotomy stretching during haptic positioning? (7) How was the experienced stability performance of the Femtis IOL after complete positioning?…”
Section: Examination Protocolmentioning
confidence: 99%